Role of Exosomes in Crosstalk Between Cancer-Associated Fibroblasts and Cancer Cells - Yang, Xi; Li, Yida; Zou, Liqing; Zhu, Zhengfei (Frontiers in Oncology, 2019)
Cancer-associated fibroblasts (CAFs) are important cells of the tumor microenvironment that can communicate with tumor cells through various mechanisms. Recently, increasing studies have found that exosomes transmit biological information by carrying microRNAs, lncRNAs, proteins, metabolites, and other substances, and thus exert biological and therapeutic effects. CAF-secreted exosomes can also affect the tumor phenotype, while the exosomes released by tumor cells can activate CAFs. Here, we review the role of exosomes in the crosstalk between CAFs and tumor cells and elaborate its mechanism.